2016
DOI: 10.1123/jpah.2015-0399
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Physical Activity and Community Health: Evidence From U.S. Counties

Abstract: In line with the social-ecological model, our findings provide the first evidence for the health benefits of county-level physical activity. Our results support extant research that has shown relationships between physical activity and individual-level, health-related outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…Some of these reviews have additionally concluded that the evidence is sufficiently robust to recommend incorporating built environment factors, including walkability, into urban design, transportation, and health planning [ 84 , 85 ]. However, this evidence base is largely derived using individual-level studies that measure walkability at micro-environmental spatial scales [ 28 ], which has raised concerns about its validity for population-level action [ 32 ]. Our results indicate that increasing macro-environmental walkability at the postal area level is positively associated with population-levels of sufficient walking to improve health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these reviews have additionally concluded that the evidence is sufficiently robust to recommend incorporating built environment factors, including walkability, into urban design, transportation, and health planning [ 84 , 85 ]. However, this evidence base is largely derived using individual-level studies that measure walkability at micro-environmental spatial scales [ 28 ], which has raised concerns about its validity for population-level action [ 32 ]. Our results indicate that increasing macro-environmental walkability at the postal area level is positively associated with population-levels of sufficient walking to improve health.…”
Section: Discussionmentioning
confidence: 99%
“…Greater use of objective walkability indexes has demonstrably progressed our understanding of environment-behavior relations through a focusing of research and inference at increasingly finer spatial resolutions (see reviews [ 10 , 11 , 29 31 ]). However, this has contributed to an evidence base derived at geographic scales substantially smaller than those used for population health policy, planning, and intervention; assumes individual-level environment-behavior relations scale to populations; and raised concerns about the utility of micro-level evidence for macro-level health programming [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Much of this evidence comes from individual-level studies of participants and the micro (personal) and meso (neighbourhood) environments in which they live [ 21 , 30 ]. However, there is increasing interest in meso (area) environment walkability, its contributions to the distribution of health within populations, and how it may be used to inform population health programming at larger regional scales [ 8 , 23 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Murray et al (2019) suggested that when golf spectators were informed about the potential health benefits of golf spectatorship, they showed greater interest in participating in and spectating golf. Sato et al (2016a) stated that the pleasant aspect of physical activity is likely to bring about good feelings in life, which might be conducive to self-rated health and life satisfaction. To sum up, higher step counts may be associated with higher levels of health perception and life satisfaction as spectators with higher step counts are more conscious about their health outcomes.…”
Section: Spectator Services and Life Satisfactionmentioning
confidence: 99%